Biatrial ablation versus limited right atrial ablation for atrial fibrillation associated with atrial septal defect in adults - Jiang, Zhaolei; Ma, Nan; Yin, Hang; Ding, Fangbao; Liu, Hao; Mei, Ju (Surgery today (Tokyo, Japan), 2015)
Purpose To compare the efficacy and safety of limited right atrial ablation versus biatrial ablation for atrial fibrillation (AF) associated with atrial septal defect (ASD) in adults. Methods The subjects were 47 consecutive adult patients who underwent ASD closure with limited right atrial ablation (RA, n = 19) or biatrial ablation (BA, n = 28) for AF, between January, 2007 and December, 2012. Eighteen patients had persistent AF and 29 had long-standing persistent AF. Bipolar RF ablation was performed for all patients. Results AF ablation and ASD closure were performed successfully in all patients. The BA group had longer cardiopulmonary bypass time, aortic cross-clamp time, and hospital stay than the RA group, but the incidence of major postoperative complications was not significantly different between the groups. On discharge, normal sinus rhythm was maintained in 100 % of the BA group patients and 78.9 % of the RA group patients ( P = 0.045). By 2 years postoperatively, cumulative maintenance of normal sinus rhythm off antiarrhythmic drugs was confirmed in 87.7 ± 6.7 % of the BA group patients and 47.4 ± 11.5 % of the RA group patients ( P = 0.003). Conclusion Biatrial ablation restored and maintained sinus rhythm more effectively than limited right atrial ablation, without increasing the risk of postoperative complications for AF associated with ASD in adults.